Pengendalian Mutu Call Number pada Perpustakaan Umum Kota Jambi - Adey Sucuk Zakaria Bahar (Perpustakaan Nasional, 2022)
The Jambi City Public Library has been established since 2009 with an average of 30.000 visitors per year, except in the last 2 years due to the Covid-19 Pandemic. The Library has a total collection of 26,703 titles and 59,397 copies. As a public library that routinely serves users, the problem faced by the Library is the order of the call number. Observing this, the Library is trying to control the quality of call numbers so that there is an increase in the quality of service to users. The formulation of the problem in this study is how to control the quality of call numbers at the Library. The purpose of this study is to carry out quality control of call numbers. The methodology used in this research is qualitative descriptive approach. The results of this study formulate call number quality control applying PDCA or the Deming’ Cycle by monitoring and evaluating call numbers using two (2) approaches, (1) quality control during proccesing with stage: total shelving and daily shelving, and selection. (2) quality control of finished goods by means: validation, repair of call numbers. Also, it is necessary to adjust the SOP for Library Material Processing by adding inspection activities to existing collections, especially in the database, to ensure the books have not been processed so that there is no duplication of call numbers. The recommendation of this study is that call number quality control must be continuously implemented so that the maximum quality of user service is obtained.